A Search for OH 18 cm Emission from Intermediate-velocity Gas at High Galactic Latitudes - Allison J. Smith; D. Anish Roshi (The Astrophysical Journal, 2023)
We present search results of 22 high-latitude (∣ b ∣ > 25°) sightlines for OH 18 cm emission using the 305 m radio telescope at the Arecibo Observatory. These sightlines appear in neutral hydrogen emission at intermediate velocities −90 ≤ V _LSR ≤ −20 km s ^−1 and are predicted to have a sufficient molecular composition so as to be detectable in molecular emission. Such objects, known as intermediate-velocity molecular clouds (IVMCs), have historically been detected through ^12 CO emission. Recent studies indicate that IVMCs may be widespread in the galaxy and have important implications for models of the interstellar medium and star formation. However, we report nondetections of OH emission toward the 22 sightlines and provide stringent upper limits on the OH column density. Using available H i and A _v data in combination with existing state-of-the-art PDR models, we estimate H _2 column densities and find that they are more than an order of magnitude lower than the predicted values. We also find that the hydrogen volume density of these clouds is ≲25 cm ^−3 . In addition, we discuss the known IVMCs with previous ^12 CO detections in the context of the PDR models. Our analysis of these clouds indicates that the structure of molecular material in IVMCs is morphologically clumpy. These results motivate the need for future sensitive, on-the-fly searches (rather than targeted searches) for CO emission from IVMCs with resolutions on the order of ∼1′. High angular resolution (∼1′) H i and A _v data will also be helpful to better constrain the structure and composition of IVMCs.